After greenwashing : symbolic corporate environmentalism and society - Bowen, Frances, 1973- (New York : Cambridge University Press, 2014)
"Businesses promote their environmental awareness through green buildings, eco-labels, sustainability reports, industry pledges and clean technologies. When are these symbols wasteful corporate spin, and when do they signal authentic environmental improvements? Based on twenty years of research, three rich case studies, a strong theoretical model and a range of practical applications, this book provides the first systematic analysis of the drivers and consequences of symbolic corporate environmentalism. It addresses the indirect cost of companies' symbolic actions and develops a new concept of the 'social energy penalty' - the cost to society when powerful corporate actors limit the social conversation on environmental problems and their solutions. This thoughtful book develops a set of tools for researchers, regulators and managers to separate useful environmental information from empty corporate spin, and will appeal to researchers and students of corporate responsibility, corporate environmental strategy and sustainable business, as well as environmental practitioners"--
"Businesses are eager to promote their environmental awareness through green buildings, eco-labels, sustainability reports, industry pledges and clean technologies. When are these symbols wasteful corporate spin, and when do they signal authentic environmental improvements? Based on 20 years of research, three rich case studies, a strong theoretical model and a range of practical applications, this book provides the first systematic analysis of the drivers and consequences of symbolic corporate environmentalism. It addresses the indirect cost of companies' symbolic actions and develops a new concept of the "social energy penalty" - the cost to society when powerful corporate actors limit the social conversation on environmental problems and their solutions. This thoughtful book develops a set of tools for researchers, regulators and managers to separate useful environmental information from empty corporate spin, and will appeal to researchers and students of corporate responsibility, corporate environmental strategy and sustainable business, as well as environmental practitioners"--
Machine generated contents note: Acknowledgements; List of abbreviations; 1. Introduction; 2. After greenwashing; 3. Perspectives on symbolic corporate environmentalism; 4. Drivers and consequences of symbolic corporate environmentalism; 5. Study 1: symbolic gaps in environmental strategies; 6. Study 2: pollution control technology and the production of symbolic capital; 7. Study 3: the evolution of measurement and performance standards; 8. Measurement and methods; 9. Implications and conclusions; Notes; References; Index.
Includes bibliographical references and index.
Keywords: Business ethics; Corporations -- Environmental aspects; Industrial management -- Environmental aspects; Environmental policy; BUSINESS & ECONOMICS / Business Ethics